Stylistic Exploration of Existential and Spiritual Themes in Sitaram Adhikari’s Poem Unseen Existence - Neupane, Pravin (NPRC Journal of Multidisciplinary Research, 2024)
This study examines the application of stylistic elements in Sitaram Adhikari’s poem "Unseen Existence", focusing on how these elements enhance the poem’s thematic depth and philosophical significance. Through a detailed analysis of diction, tone, imagery, symbolism, structure, and rhythm, the research explores how Adhikari conveys the existential and spiritual themes central to the poem. The reflective tone and symbolic imagery engage readers, prompting introspection about their relationship with an unseen guiding force. The findings highlight the interplay between style and meaning, demonstrating how stylistic devices amplify the poem’s universal relevance. Additionally, the study underscores Adhikari’s contribution to Nepali literature, showcasing his ability to bridge traditional spiritual concepts with modern poetic techniques. This research offers valuable insights into the stylistic richness of contemporary Nepali poetry, paving the way for further exploration of literary craftsmanship in philosophical and existential contexts.